Formation of tin-tin oxide core-shell nanoparticles in the composite SnO2−x/nitrogen-doped carbon nanotubes by pulsed ion beam irradiation; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 394 - Korusenko P. M.; Nesov S. N. Sergey Nikolaevich; Bolotov V. V. Valery Viktorovich; Povoroznyuk S. N. Sergey Nikolaevich; Pushkarev A. I. Aleksandr Ivanovich; Ivlev K. E. Konstantin Evgenjevich; Smirnov D. A. Dmitry Aanatoljevich (2017, 2017)
Title screen